2023
DOI: 10.1021/acs.inorgchem.2c03520
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Acetylacetonate (acac) and β-Ketoiminate (acnac) Complexes of Uranium

Abstract: Transmetalation of potassium salts of differently substituted acetylacetonate (acac) and β-ketoiminate (acnac) with [U(I) 3 (dioxane) 1.5 ] and [U(I) 4 (dioxane) 2 ] resulted in the formation of homoleptic, octahedral complexes [U( tBu acnac Ph ) 3 ] (with tBu acnac Ph = 2,2,6,6-tetramethyl-5-(phenylimino)heptan-3-onate) in the oxidation states +III and +IV and the homoleptic, square prismatic complexes [U IV ( Me acnac Ph ) 4 ] (with Me acnac Ph = 4-(phenylimino)pentan-2-onate) and the homoleptic, square anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Very recently, Meyer's group reported synthesis and characterization of homoleptic β-diketonato and β-ketoiminato complexes of U ions in different oxidation states to develop reversible redox couples for URFB. 97 In most cases, U 4+ compounds such as [U IV ( t Bu acnac Ph ) 3 ] + , [U IV ( Me acnac Ph ) 4 ], and [U IV ( t Bu ac Me ac) 4 ] (Fig. 12a) are formed, but the corresponding U 3+ and U 5+ species may also be accessible through chemical reactions under appropriately selected conditions.…”
Section: Utilization Of Depleted Uraniummentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Meyer's group reported synthesis and characterization of homoleptic β-diketonato and β-ketoiminato complexes of U ions in different oxidation states to develop reversible redox couples for URFB. 97 In most cases, U 4+ compounds such as [U IV ( t Bu acnac Ph ) 3 ] + , [U IV ( Me acnac Ph ) 4 ], and [U IV ( t Bu ac Me ac) 4 ] (Fig. 12a) are formed, but the corresponding U 3+ and U 5+ species may also be accessible through chemical reactions under appropriately selected conditions.…”
Section: Utilization Of Depleted Uraniummentioning
confidence: 99%
“…Fig. 12 Schematic structures of [U IV ( tBu acnac Ph ) 3 ] + , [U IV ( Me acnac Ph ) 4 ], and [U IV ( tBu ac Me ac) 4 ] complexes studied by Waldschmidt et al (a) and cyclic voltammograms of [U IV ( tBu ac Me ac) 4 ] in benzene/MeCN 1 : 1 solution with ∼0.1 M [N(nBu) 4 ][PF 6 ] at 200 mV s −1 potential sweep rate (b) 97. Reprinted with permission from American Chemical Society (Copyright 2023).…”
mentioning
confidence: 99%
“…25,26 Nevertheless, the exploration of the reactivity between U(III) or U(IV) and substituted acetylacetonate (acac)/β-ketoiminate ligands led to the isolation of trivalent, tetravalent, and pentavalent homoleptic uranium complexes, wherein the ligands were found to be redox-innocent. 27 Recently, Carpenter et al reported two homoleptic complexes of uranium with bis(mesitoyl)phosphide ( mes BAP) and bis-(2,4,6-triisopropylbenzoyl)phosphide ( tripp BAP) ligands. 28 The bis(acyl)phosphide (BAP) ligand is analogous to the acac ligand (see Figure 1a).…”
mentioning
confidence: 99%
“…Interestingly, when a redox-active benzophenone ligand reacted with U 3+ , it resulted in the reduction of the carbonyl bonds, yielding ketyl radicals. This led to elongation of the CO bonds. β-diketonate ligands possessing CO bonds were also found to be redox-active in chromium complexes. , Nevertheless, the exploration of the reactivity between U­(III) or U­(IV) and substituted acetylacetonate (acac)/β-ketoiminate ligands led to the isolation of trivalent, tetravalent, and pentavalent homoleptic uranium complexes, wherein the ligands were found to be redox-innocent . Recently, Carpenter et al reported two homoleptic complexes of uranium with bis­(mesitoyl)­phosphide ( mes BAP) and bis­(2,4,6-triisopropylbenzoyl)­phosphide ( tripp BAP) ligands .…”
mentioning
confidence: 99%